A woman's world at a time of war : an analysis of selected women's diaries during the Anglo-Boer War 1899-1902 - Ross, Helen M. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (History))--University of Stellenbosch, 2006.